An outbreak of carbapenem-resistant Acinetobacter baumannii in a COVID-19 dedicated hospital. Issue 1 (March 2021) - Gottesman, Tamar; Fedorowsky, Rina; Yerushalmi, Rebecca; Lellouche, Jonathan; Nutman, Amir
Summary: We describe an outbreak of carbapenem-resistant Acinetobacter baumannii (CRAB) in a COVID-19 dedicated hospital. The suspected mechanism of transfer was an environmental source that persisted despite evacuation and terminal cleaning of the entire hospital, and transmitted through healthcare workers' hands or equipment. This outbreak demonstrates that practices to prevent the spread of multidrug-resistant organisms must not be neglected during the COVID-19 pandemic.